Identifying the cortical substrates of interictal epileptiform activity in patients with extratemporal epilepsy: An EEG‐fMRI sequential analysis and FDG‐PET study. (30th January 2013) - Donaire, Antonio; Capdevila, Antoni; Carreño, Mar; Setoain, Xavier; Rumià, Jordi; Aparicio, Javier; Campistol, Jaume; Padilla, Nelly; Sanmartí, Francesc; Vernet, Oriol; Pintor, Luis; Boget, Teresa; et al.
Summary Purpose The aim of this study was to apply sequential analysis of electroencephalography–functional magnetic resonance imaging (EEG‐fMRI) data to study the cortical substrates related to the generation of the interictal epileptiform activity (IEA) in patients with pharmacoresistant extratemporal epilepsy. Methods We analyzed fMRI data from 21 children, adolescents, and young adults patients who showed frequent bursts or runs of spikes on EEG, by using the sequential analysis method. We contrasted consecutive fixed‐width blocks of 10 s to obtain the relative variations in cerebral activity along the entire fMRI runs. Significant responses (p < 0.05, family‐wise error (FWE) corrected), time‐related to the IEA recorded on scalp EEG, were considered potential IEA cortical sources. These results were compared with those from the fluorodeoxyglucose–positron emission tomography (FDG‐PET), intracranial EEG (two patients), and surgery outcome (eight patients). Key Findings The typical IEA was recorded in all patients. After the sequential analysis, at least one significant blood oxygen level–dependent (BOLD) response spatially consistent with the presumed epileptogenic zone was found. These IEA‐related activation areas coincided when superimposed with the hypometabolism depicted by the FDG‐PET. These data were also consistent with the invasive EEG findings. Epileptic seizures were recorded in eight patients. A subset of IEA‐associated fMRI activations was consistent the activations at seizure‐onset determined by sequential analysis. The inclusion of the IEA‐related areas in the resection rendered the patients seizure‐free (five of eight operated patients). Significance The EEG‐fMRI data sequential analysis could noninvasively identify cortical areas involved in the IEA generation. The spatial relationship of these areas with the cortical metabolic abnormalities depicted by the FDG‐PET and their intrinsic relationship regarding the ictal‐onset zone could be useful in epilepsy surgery planning.